PENGARUH KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN NON-MEDIS DI RSUD AL IHSAN PROVINSI JAWA BARAT - Widwi Handari Adji; Wulan Ramdiani; Wilma Zuarko Adji (INFOKES (Informasi Kesehatan), 2020)
The purpose of this research was aim the influence of the organization commitment to the turnover intention to a non-medical employees at RSUD Al Ihsan West Java Province. This research use descriptive method with quantitative approach. Data collection technique used by observation and literature study are questionnaire and interview with the research subject is the employees many as 32. The result of this research shows correlation is 0,944 means that the organization commitment and turnover intention has a very strong relationship. And a great variable of the organization commitment to turnover intention is 89,1% and the remaining 10,9% influenced by another factor as Job satisfaction, workspace, stress work, as well individual characteristics. The problems found in this research are: (1) low of employment, (2) lack of a sense of pride in the organization, (3) low of organization commitment, (4) luck of loyalty to the organization. The suggestion from the writer are: (1) gives the employees an opportunity to demonstrate creativity and innovation, (2) giving employees opportunity to develop themselves and career, (3) give appreciation to employees, (4) giving a trust, a duty and a responsibility to employees.